A preliminary study on the element abundance in the Hulusimpang Formation, Way Kalianda, Pesawaran, Lampung, Indonesia. Issue 1 (November 2021) - Harbowo, D G; Priadi, B; Julian, T; Amelia, R N; Sihombing, D J P; Kencana, F S
Abstract: Hulusimpang Formation.has known as Oligocene-Miocene rocks that consisted of volcanoclastic rock. Its scope was wide, especially in southern Sumatra. This formation is supposed as a prospect host of various hydrothermal mineralization. A preliminary study was carried out to examine the abundance of elements located in Way Kalianda River, Pesawaran, Lampung. This study was conducted by easuring its stratigraphy and analyzing its composition using an X-Ray fluorescence analyzer. The lithologies generally consist of lapilli tuffs, volcanic breccias, interbeded by claystone and sandstone; in addition, it is also frequently found petrified wood and andesitic-lithic fragments. As a result, the significant abundant elements are Fe (35.5%), Si (27.9%), Al (17.4%), K (6.7%), Cl (5.5%), Ti (1.7%), and Ca (1.5%) and also Mn, Ag, P, Mg, Sr, Zr, and Co. It also presents trace elements such as Rb, Zn, Pb, Te, V, Ba, Cr, Sn, Ni, Ga, Nb, Mo, and Eu. These elements are suggested from distal facies of intermediates-magma series Tertiary volcano.